VD_FINDINFO AI 378/09 - 398/2011 vom 9. November 1992 - VD Tribunal cantonal (1992)
MOTIF DE RÉVISION, RÉVISIONDÉCISION, RENTE D'INVALIDITÉ, TENUE DU MÉNAGE | 28 LAI, 28a LAI, 4 al. 1 LAI, 16 LPGA, 7 al. 1 LPGA, 8 al. 1 LPGA, 8 al. 3 LPGA, 88a al. 1 RAI